2014
DOI: 10.3389/fpls.2014.00261
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive set of transcript sequences of the heavy metal hyperaccumulator Noccaea caerulescens

Abstract: Noccaea caerulescens is an extremophile plant species belonging to the Brassicaceae family. It has adapted to grow on soils containing high, normally toxic, concentrations of metals such as nickel, zinc, and cadmium. Next to being extremely tolerant to these metals, it is one of the few species known to hyperaccumulate these metals to extremely high concentrations in their aboveground biomass. In order to provide additional molecular resources for this model metal hyperaccumulator species to study and understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 70 publications
2
43
0
Order By: Relevance
“…Based on our biomass data, it seemed that NAV did not grow well in multiple experiments under the control conditions in our hydroponic system, thus, the Zn or phloem-specific iron transporter that is essential for systemic iron signalling and redistribution of iron and cadmium in A. thaliana (Zhai et al, 2014). Large variations in the region ( between 500 nucleotides up-and downstream of this gene) were detected between populations, Five of these were found to result in amino acid changes in the conserved region of the protein (Supplement 1).This gene was also found to be differently expressed under metal stress in N. caerulescens (Halimaa et al, 2014a;Lin et al, 2014). In addition, we found also a non-synonymous SNP in the transcription factor WRKY72, which has a role in plant abiotic stresses like Pi deprivation, salt and drought (Yu et al, 2010;Chen et al, 2012b;Niu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on our biomass data, it seemed that NAV did not grow well in multiple experiments under the control conditions in our hydroponic system, thus, the Zn or phloem-specific iron transporter that is essential for systemic iron signalling and redistribution of iron and cadmium in A. thaliana (Zhai et al, 2014). Large variations in the region ( between 500 nucleotides up-and downstream of this gene) were detected between populations, Five of these were found to result in amino acid changes in the conserved region of the protein (Supplement 1).This gene was also found to be differently expressed under metal stress in N. caerulescens (Halimaa et al, 2014a;Lin et al, 2014). In addition, we found also a non-synonymous SNP in the transcription factor WRKY72, which has a role in plant abiotic stresses like Pi deprivation, salt and drought (Yu et al, 2010;Chen et al, 2012b;Niu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…caerulescens (Halimaa et al, 2014;Lin et al, 2014), and by comparative transcriptomic analysis in A. thaliana and A. halleri (Becher et al, 2004;Weber et al, 2004Weber et al, , 2006 or A. thaliana and N. caerulescens (Rigola et al, 2006;Hammond et al, 2006;van de Mortel et al, 2006;van de Mortel et al, 2008;Plessl et al, 2010). These studies have revealed many genes that are overexpressed in Zn/Cd hyperaccumulator species compared to A. thaliana, which may therefore be related to the variation in Zn/Cd accumulation and tolerance among different species.…”
Section: Molecular Mechanisms Of Metal Tolerance and Hyperaccumulationmentioning
confidence: 99%
See 3 more Smart Citations